Harmonisasi Kepemimpinan Tradisional: Daud Sebagai Model Inspiratif Dalam Pelayanan Gembala Masa Kini - Irmesyanti Irmesyanti; Meylani Tandi Allo; Jeny Ekaristi; Mithaliyani Jeika Massa (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Harmonization of traditional leadership, especially through the figure of David, opens up opportunities and challenges in the context of modern pastoral ministry. Values ​​such as courage, perseverance, and integrity serve as inspiration for church leaders. A strategic approach, involving coaching and training, is crucial to integrating these values. Despite challenges and resistance, a deep understanding of these factors helps design effective strategies. By applying values ​​in daily practice, church leaders create enduring, relevant, and inspiring ministries, guiding people toward spiritual growth.